Computed tomography demonstration of the complications and associations of lymphobronchial tuberculosis in children - Lucas, Susanna (My University, 2012)
Lymphobronchial tuberculosis (LBTB) is tuberculous lymphadenopathy involving the airways, which is particularly common in children. AIM: To describe the CT findings of LBTB in children, the parenchymal complications and associated abnormalities. METHOD: CT scans of 98 children with LBTB were retrospectively reviewed. Lymphadenopathy, bronchial narrowing, parenchymal complications and associations were documented. RESULTS: Infants comprised 51% of patients. The commonest lymphadenopathy was subcarinal (97% of patients). Bronchial compressions (259 in total) were present in all patients, of which 23% were severe / complete stenoses and 28% affected bronchus intermedius. Parenchymal complications were present in 94% of patients, including consolidation (88%), breakdown (42%), air trapping (38%), expansile pneumonia (28%), collapse (17%) and bronchiectasis (9%), all predominantly right-sided (63%). Associations included oval focal bodies, miliary nodules, pleural disease and intracavitory bodies. CONCLUSIONS: The most important CT finding of children with LBTB is visible airway compression as a result of lymphadenopathy. CT of children with LBTB showed that airway compressions were more severe in infants and most commonly involved bronchus intermedius. Numerous parenchymal complications were documented, all showing rightsided predominance. Several associations were identified.
M.Med. (Radiology), Faculty of Health Sciences, University of the Witwatersrand, 2011
Keywords: Tuberculosis-- in infancy & childhood; Tomography, X-Ray Computed